Solid waste-based recycled concrete and preparation method thereof
Through the coordinated strengthening method of impregnating the regenerated crude aggregate with oxalic acid solution and vacuum impregnating the nano-silica epoxy emulsion, the problem of insufficient performance of the regenerated aggregate concrete is solved, and its impermeability and strength are significantly improved.
Patent Information
- Application Number
- CN202510150676.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2045-02-11
AI Technical Summary
The performance of recycled aggregate concrete is insufficient, mainly due to the adhesion of old mortar on the surface of recycled aggregate, resulting in strong water absorption, high porosity, low strength, and extremely weak bonding performance in the transition zone of the aggregate-mortar interface.
By using the crushed waste concrete as regenerated coarse aggregate, after impregnation in the oxalic acid solution, vacuum impregnation is performed using nanosilica epoxy emulsion to enhance the strength and impermeability of the regenerated coarse aggregate.
It significantly improves the permeability and strength of recycled concrete, improves the bonding performance of the aggregate-mortar interface transition zone, and improves the overall performance of recycled concrete.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and specifically relates to solid waste-based recycled concrete and a preparation method thereof. Background Art
[0002] Recycled aggregate concrete technology is one of the most common and direct ways to recycle construction waste resources. However, compared with natural aggregate concrete, recycled aggregate concrete has obvious performance deficiencies. The main reason is that the surface of recycled coarse aggregate is adhered to old mortar, which has defects such as strong water absorption, high porosity and low strength. During pouring, an aggregate-mortar interface transition zone (ITZ) with complex microstructure and abnormally weak bonding performance is formed between the recycled coarse aggregate and the new mortar, resulting in reduced performance of recycled aggregate concrete.
[0003] At present, the performance improvement technology of recycled concrete is mainly focused on the modification of recycled aggregates, including physical and chemical methods. Physical strengthening, that is, using mechanical equipment to reprocess the simply crushed recycled aggregates without changing the microstructure and physical properties of the recycled aggregates, to remove the cement mortar adhering to the surface of the recycled aggregates and the edges and corners of the particles with weak connections. Chemical strengthening, that is, using chemical reagent immersion and other means to change the microstructure and physical properties of the ITZ of the recycled aggregates, so that the ITZ is modified and strengthened. At present, there are many studies on the strengthening methods of recycled aggregates, and the principles are different, but most of them are cumbersome procedures, high costs, and difficult to promote and apply in engineering. Summary of the invention
[0004] The object of the present invention is to provide a solid waste-based recycled concrete and a preparation method thereof. By using crushed waste concrete as recycled coarse aggregate and strengthening the recycled coarse aggregate, not only the porosity of the recycled coarse aggregate is reduced, the impermeability of the obtained recycled concrete is improved, but also the strength of the recycled coarse aggregate can be enhanced, the interface transition zone between the recycled coarse aggregate and the mortar can be improved, and the performance of the recycled concrete can be greatly improved. The raw materials used in the present invention are common, low in price, and have excellent strengthening effects on recycled coarse aggregate, and have broad prospects for promotion and application.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions of the present invention is to provide a method for strengthening recycled coarse aggregate, comprising the following steps:
[0007] The recycled coarse aggregate from the waste concrete source is immersed in an oxalic acid solution, the water is drained, and then vacuum immersed in a nano-silicon dioxide epoxy emulsion, and then solidified after being fished out, so as to complete the strengthening of the recycled coarse aggregate.
[0008] The invention firstly utilizes oxalic acid to impregnate the recycled coarse aggregate, so that the nano-silicon dioxide epoxy emulsion can be better immersed in the recycled coarse aggregate. The nano-silicon dioxide epoxy emulsion is selected as the reinforcing solution. On the one hand, the nano-silicon dioxide and the cured epoxy resin can effectively increase the strength of the recycled coarse aggregate. On the other hand, the film formed by the nano-silicon dioxide epoxy emulsion on the surface of the recycled coarse aggregate can also enhance the anti-seepage performance of the recycled coarse aggregate, and can better adhere to the concrete mortar, enhance the interface transition zone, and obtain high-performance concrete.
[0009] Preferably, the particle size of the recycled coarse aggregate is 5 to 25 mm.
[0010] Preferably, the concentration of the oxalic acid solution is 1 to 1.5 mol / L.
[0011] Preferably, the vacuum degree of the vacuum impregnation is 0.05-0.08 MPa, and the time is 30-60 min.
[0012] Preferably, the content of nano-silicon dioxide in the nano-silicon dioxide epoxy emulsion is 5-12wt.%, the water content is 10-20wt.%, and the mass ratio of epoxy resin, curing agent and emulsifier is 2:1-1.5:1-1.5.
[0013] Optionally, the epoxy resin in the nano-silicon dioxide epoxy emulsion is bisphenol A epoxy resin, the curing agent is isophorone diamine (IPDA), and the emulsifier is sodium dodecylbenzene sulfonate.
[0014] The second technical solution of the present invention is to provide a recycled coarse aggregate obtained according to the above-mentioned recycled coarse aggregate strengthening method.
[0015] The third technical solution of the present invention is to provide a solid waste-based recycled concrete, which comprises, by weight, 25 to 35 parts of a composite cementitious material, 40 to 60 parts of the above-mentioned recycled coarse aggregate, 15 to 25 parts of a fine aggregate, 0.3 to 0.8 parts of a water reducer and 8 to 12 parts of water; the composite cementitious material is obtained by mixing cement, fly ash and alkali activator in a mass ratio of 7:2:1.
[0016] Preferably, the alkaline activator is a mixture of sodium silicate and sodium hydroxide in a mass ratio of 3:1.
[0017] Preferably, the fine aggregate is river sand or machine-made sand with a fineness modulus of 2.6 to 3.0.
[0018] Preferably, the water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate is not less than 20%.
[0019] The fourth technical solution of the present invention is to provide a method for preparing the above-mentioned solid waste-based recycled concrete, comprising the following steps:
[0020] Mix cement, fly ash and alkali activator evenly, then mix them with recycled coarse aggregate and fine aggregate, then add water and water reducing agent, stir evenly to obtain solid waste-based recycled concrete.
[0021] The beneficial technical effects of the present invention are as follows:
[0022] The present invention aims at the defects that the recycled coarse aggregate from traditional waste concrete sources has strong water absorption, high porosity, low strength, and forms an aggregate-mortar interface transition zone with complex microstructure and abnormally weak bonding performance between the aggregate and the new mortar during pouring, which leads to low performance of the prepared recycled concrete. The present invention proposes a strengthening scheme of first acid leaching the recycled coarse aggregate and then vacuum impregnating the recycled coarse aggregate with nano-silicon dioxide epoxy emulsion. Through the synergistic strengthening of acid leaching and vacuum impregnation with nano-silicon dioxide epoxy emulsion, the strength of the recycled coarse aggregate is significantly improved, its water absorption and porosity are reduced, and the interface transition zone between the recycled coarse aggregate and the new mortar in the recycled concrete prepared with the recycled coarse aggregate as raw material is improved.
[0023] The recycled coarse aggregate strengthening scheme provided by the present invention is simple, and the prepared recycled concrete has high performance strength and good impermeability. The scheme has good prospects for promotion and application. DETAILED DESCRIPTION
[0024] With the acceleration of urbanization, a large amount of construction waste is generated, of which waste concrete accounts for a large proportion. Traditional treatment methods such as landfill not only occupy land, but also pollute the environment. Crushing and screening waste concrete as recycled coarse aggregate for new concrete preparation is an effective way to realize the resource utilization of construction waste.
[0025] Waste concrete as recycled coarse aggregate has significant advantages in the construction field, which are mainly reflected in the following aspects:
[0026] 1. Resource conservation and recycling
[0027] Reduce the consumption of natural resources: Recycled coarse aggregate can replace natural sand and gravel, reduce the demand for mining of non-renewable resources (such as natural gravel and rock), and alleviate the pressure of resource depletion.
[0028] Recycling of construction waste: Waste concrete accounts for 30% to 50% of the total construction waste. Recycling can significantly reduce the amount of landfill and improve resource recycling efficiency.
[0029] 2. Environmental protection
[0030] Reduced carbon emissions: Compared with the mining and transportation of natural aggregates, the production of recycled coarse aggregates requires less energy and has lower carbon emissions (research shows that it can reduce the carbon footprint by about 20% to 30%).
[0031] Reduce land occupation and pollution: avoid the damage of construction waste landfill to soil, groundwater and ecological environment, and alleviate the problem of "garbage siege".
[0032] 3. Economic benefits
[0033] Cost advantage: The production cost of recycled coarse aggregate is usually lower than that of natural aggregate (especially in areas where natural resources are scarce or the transportation distance is long).
[0034] 4. Technical performance applicability
[0035] Meeting low to medium strength requirements: Recycled coarse aggregate can be used in non-structural or low-strength concrete (such as roadbed, floor, filling layer), and its performance can be further improved by optimizing the mix ratio or pretreatment (such as strengthening, removing impurities).
[0036] Mixed with natural aggregate: When partially replacing natural aggregate (such as 30% to 50% ratio), the mechanical properties of concrete (compressive strength, durability) can still meet the engineering requirements.
[0037] 5. Promote sustainable development
[0038] Comply with green building standards: Certification systems such as LEED and BREEAM encourage the use of recycled materials and improve the project's environmental rating.
[0039] Promote circular economy: form a closed-loop model of "demolition-regeneration-new construction" to help the construction industry transform towards low-carbon development.
[0040] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0041] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0042] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0043] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0044] The "parts" mentioned in the embodiments of the present invention refer to parts by mass.
[0045] Example 1
[0046] Preparation of solid waste-based recycled concrete:
[0047] (1) The waste concrete from the construction site is manually crushed and then put into a jaw concrete crusher to screen out particles with a particle size of 5 to 25 mm. The screened particles are immersed in an oxalic acid solution with a concentration of 1 mol / L, taken out after 24 hours, and the water is drained;
[0048] (2) taking 100 parts of bisphenol A epoxy resin and 20 parts of nano-silicon dioxide and stirring them evenly, then adding 50 parts of curing agent IPDA, stirring evenly, and then adding emulsifier sodium dodecylbenzene sulfonate, stirring evenly, and then slowly adding 40 parts of water while performing high-speed shearing to obtain a nano-silicon dioxide epoxy emulsion;
[0049] (3) adding the particles obtained after acid leaching in step (1) to the nano-silica epoxy emulsion obtained in step (2), immersing for 60 minutes under a vacuum degree of 0.08 MPa, removing and curing to obtain modified recycled coarse aggregate;
[0050] (4) Take 70 parts of PO42.5 cement and fly ash (specific surface area 650m 2 / kg) 20 parts, 7.5 parts of sodium silicate and 2.5 parts of sodium hydroxide are mixed evenly, and then 200 parts of modified recycled coarse aggregate and 80 parts of machine-made sand with a fineness modulus of 2.6 are added and mixed evenly, and finally 3 parts of polycarboxylic acid high-efficiency water reducing agent (water reduction rate 25%) and 40 parts of water are added and mixed evenly to obtain solid waste-based recycled concrete.
[0051] Example 2
[0052] Preparation of solid waste-based recycled concrete:
[0053] (1) The waste concrete from the construction site is manually crushed and then put into a jaw concrete crusher to screen out particles with a particle size of 5 to 25 mm. The screened particles are immersed in an oxalic acid solution with a concentration of 1 mol / L, taken out after 24 hours, and the water is drained;
[0054] (2) taking 100 parts of bisphenol A epoxy resin and 18 parts of nano-silicon dioxide and stirring them evenly, then adding 50 parts of curing agent IPDA, stirring evenly, and then adding emulsifier sodium dodecylbenzene sulfonate, stirring evenly, and then slowly adding 40 parts of water while performing high-speed shearing to obtain a nano-silicon dioxide epoxy emulsion;
[0055] (3) adding the particles obtained after acid leaching in step (1) to the nano-silica epoxy emulsion obtained in step (2), immersing for 60 minutes under a vacuum degree of 0.08 MPa, removing and curing to obtain modified recycled coarse aggregate;
[0056] (4) Take 70 parts of PO42.5 cement and fly ash (specific surface area 650m 2 / kg) 20 parts, 7.5 parts of sodium silicate and 2.5 parts of sodium hydroxide are mixed evenly, and then 180 parts of modified recycled coarse aggregate and 75 parts of machine-made sand with a fineness modulus of 2.6 are added and mixed evenly, and finally 3 parts of polycarboxylic acid high-efficiency water reducing agent (water reduction rate 25%) and 38 parts of water are added and mixed evenly to obtain solid waste-based recycled concrete.
[0057] Comparative Example 1
[0058] Preparation of solid waste-based recycled concrete (compared with Example 1, the acid leaching process was omitted):
[0059] (1) The waste concrete from the construction site is manually crushed and then put into a jaw concrete crusher to screen out particles with a particle size of 5 to 25 mm;
[0060] (2) taking 100 parts of bisphenol A epoxy resin and 20 parts of nano-silicon dioxide and stirring them evenly, then adding 50 parts of curing agent IPDA, stirring evenly, and then adding emulsifier sodium dodecylbenzene sulfonate, stirring evenly, and then slowly adding 40 parts of water while performing high-speed shearing to obtain a nano-silicon dioxide epoxy emulsion;
[0061] (3) adding the particles sieved out in step (1) to the nano-silica epoxy emulsion prepared in step (2), immersing for 60 min under a vacuum degree of 0.08 MPa, removing and curing to obtain modified recycled coarse aggregate;
[0062] (4) Take 70 parts of PO42.5 cement and fly ash (specific surface area 650m 2 / kg) 20 parts, 7.5 parts of sodium silicate and 2.5 parts of sodium hydroxide are mixed evenly, and then 200 parts of modified recycled coarse aggregate and 80 parts of machine-made sand with a fineness modulus of 2.6 are added and mixed evenly, and finally 3 parts of polycarboxylic acid high-efficiency water reducing agent (water reduction rate 25%) and 40 parts of water are added and mixed evenly to obtain solid waste-based recycled concrete.
[0063] Comparative Example 2
[0064] Preparation of solid waste-based recycled concrete (compared with Example 1, the addition of nano-silicon dioxide is omitted):
[0065] (1) The waste concrete from the construction site is manually crushed and then put into a jaw concrete crusher to screen out particles with a particle size of 5 to 25 mm. The screened particles are immersed in an oxalic acid solution with a concentration of 1 mol / L, taken out after 24 hours, and the water is drained;
[0066] (2) Take 100 parts of bisphenol A epoxy resin and 50 parts of curing agent IPDA, stir them evenly, then add emulsifier sodium dodecylbenzene sulfonate, stir them evenly, and then slowly add 40 parts of water while performing high-speed shearing to prepare epoxy emulsion;
[0067] (3) adding the particles obtained after acid leaching in step (1) to the epoxy emulsion obtained in step (2), immersing for 60 minutes under a vacuum degree of 0.08 MPa, removing and curing to obtain modified recycled coarse aggregate;
[0068] (4) Take 70 parts of PO42.5 cement and fly ash (specific surface area 650m 2 / kg) 20 parts, 7.5 parts of sodium silicate and 2.5 parts of sodium hydroxide are mixed evenly, and then 200 parts of modified recycled coarse aggregate and 80 parts of machine-made sand with a fineness modulus of 2.6 are added and mixed evenly, and finally 3 parts of polycarboxylic acid high-efficiency water reducing agent (water reduction rate 25%) and 40 parts of water are added and mixed evenly to obtain solid waste-based recycled concrete.
[0069] Comparative Example 3
[0070] Preparation of solid waste-based recycled concrete:
[0071] (1) The waste concrete from the construction site is manually crushed and then put into a jaw concrete crusher to screen out particles with a particle size of 5 to 25 mm to obtain recycled coarse aggregate;
[0072] (2) Take 70 parts of PO42.5 cement and fly ash (specific surface area 650m 2 / kg) 20 parts, 7.5 parts of sodium silicate and 2.5 parts of sodium hydroxide are mixed evenly, and then 200 parts of recycled coarse aggregate and 80 parts of machine-made sand with a fineness modulus of 2.6 are added and mixed evenly, and finally 3 parts of polycarboxylic acid high-efficiency water reducing agent (water reduction rate 25%) and 40 parts of water are added and mixed evenly to obtain solid waste-based recycled concrete.
[0073] The 28d compressive strength of the solid waste-based recycled concrete prepared in Examples 1 to 2 and Comparative Examples 1 to 3 was measured according to GB / T 50081-2002, and the measurement results are shown in Table 1; the 28d chloride ion diffusion coefficient m of the solid waste-based recycled concrete prepared in Examples 1 to 2 and Comparative Examples 1 to 3 was measured according to GB / T 31289-2014. 2 / s, the measurement results are shown in Table 1.
[0074] Table 1 Test results of strength and impermeability of recycled concrete
[0075] 28d compressive strength MPa <![CDATA[28d chloride ion diffusion coefficient m 2 / s]]> Example 1 48.5 <![CDATA[6.84×10 -12 ]]> Example 2 47.4 <![CDATA[6.35×10 -12 ]]> Comparative Example 1 44.1 <![CDATA[1.36×10 -11 ]]> Comparative Example 2 42.2 <![CDATA[1.07×10 -11 ]]> Comparative Example 3 32.1 <![CDATA[3.96×10 -11 ]]>
[0076] It can be seen from Table 1 that the recycled coarse aggregate strengthening method provided by the present invention can improve the strength and impermeability of the recycled concrete prepared therefrom, and the pickling and nano-silica epoxy emulsion impregnation of the present invention have a synergistic effect.
[0077] The water absorption, crushing value and porosity of the recycled coarse aggregate or modified recycled coarse aggregate used in preparing the solid waste-based recycled concrete of Examples 1 to 2 and Comparative Examples 1 to 3 were measured, and the measurement results are shown in Table 2.
[0078] Among them, the water absorption rate is the proportion of weight increase of coarse aggregate after absorbing water, the crushing value is measured by a crushing value measuring instrument, and the porosity is measured by a vacuum adsorption method.
[0079] The crushing value determination steps are as follows: level the surface of the sample in the cylinder, install the pressure head, place it on the testing machine, evenly load it to 200KN within 160-300s, stabilize it for 5s, then unload it and take out the measuring cylinder. Pour out the sample in the cylinder and weigh its mass (m 0 ), use a square hole sieve with a diameter of 2.50 mm to screen out the crushed fine particles, and weigh the mass of the sample remaining on the sieve (m 1 ), crushing value (%) = (m 0 -m 1 ) / m 0 ×100%.
[0080] Table 2 Determination results of water absorption, crushing value and porosity of coarse aggregate
[0081] Water absorption % Crushing value% Porosity % Example 1 8.3 11.3 7.3 Example 2 8.6 12.1 7.5 Comparative Example 1 9.9 14.2 8.9 Comparative Example 2 9.3 13.7 8.6 Comparative Example 3 13.4 24.2 15.9
[0082] It can be seen from Table 2 that acid leaching first and then impregnation with nano-silica epoxy emulsion can significantly reduce the water absorption and porosity of recycled coarse aggregate and improve its strength; the nano-silica in the nano-silica epoxy emulsion has a positive effect on reducing the water absorption and porosity of the recycled coarse aggregate and improving its strength; whether the recycled coarse aggregate is acid-leached before impregnating the recycled coarse aggregate with nano-silica epoxy emulsion has a significant effect on the water absorption, porosity and strength of the recycled coarse aggregate.
[0083] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for strengthening recycled coarse aggregate, characterized in that: The following steps are involved: The recycled coarse aggregate from the waste concrete source is immersed in an oxalic acid solution, the water is drained, and then vacuum immersed in a nano-silicon dioxide epoxy emulsion, and then solidified after being fished out, so as to complete the strengthening of the recycled coarse aggregate.
2. The method for strengthening recycled coarse aggregate according to claim 1, characterized in that: The particle size of the recycled coarse aggregate is 5 to 25 mm.
3. The method for strengthening recycled coarse aggregate according to claim 1, characterized in that: The concentration of the oxalic acid solution is 1-1.5 mol / L.
4. The method for strengthening recycled coarse aggregate according to claim 1, characterized in that: The vacuum degree of the vacuum impregnation is 0.05-0.08 MPa, and the time is 30-60 minutes.
5. The method for strengthening recycled coarse aggregate according to claim 1, characterized in that: The nano-silicon dioxide content in the nano-silicon dioxide epoxy emulsion is 5-12wt.%, the water content is 10-20wt.%, and the mass ratio of the epoxy resin, the curing agent and the emulsifier is 2:1-1.5:1-1.
5.
6. A recycled coarse aggregate obtained by the method for strengthening recycled coarse aggregate according to any one of claims 1 to 5.
7. A solid waste-based recycled concrete, characterized in that: The components include, by mass, 25 to 35 parts of composite cementitious material, 40 to 60 parts of recycled coarse aggregate as claimed in claim 6, 15 to 25 parts of fine aggregate, 0.3 to 0.8 parts of water reducer and 8 to 12 parts of water; the composite cementitious material is obtained by mixing cement, fly ash and alkali activator in a mass ratio of 7:2:
1.
8. The solid waste-based recycled concrete according to claim 7, characterized in that: The alkali activator is a mixture of sodium silicate and sodium hydroxide in a mass ratio of 3:1; and / or, the fine aggregate is river sand or machine-made sand with a fineness modulus of 2.6 to 3.0; and / or, the water reducer is a polycarboxylate water reducer with a water reduction rate of not less than 20%.
9. A method for preparing solid waste-based recycled concrete according to claim 7 or 8, characterized in that: The following steps are involved: Mix cement, fly ash and alkali activator evenly, then mix them with recycled coarse aggregate and fine aggregate, then add water and water reducing agent, stir evenly to obtain solid waste-based recycled concrete.
Citation Information
Patent Citations
Recycled concrete and preparation method thereof
CN111039624A
Nano silicon dioxide and basalt fiber synergistically enhanced recycled concrete and preparation method thereof
CN114656206A
Carbonized recycled coarse aggregate concrete and preparation method thereof
CN117263580A
Preparation method and application of magnesium oxide modified and carbonized synergistically reinforced recycled coarse aggregate
CN118561537A
Recycled concrete preparation process
CN119059774A
Cited By
Recycled aggregate concrete 3D printing wall material modification process
CN120483568A
Recycled aggregate as well as preparation method and application thereof
CN121494374A
Method for improving performance of disassembled concrete part based on multi-stage synergistic repair and product thereof
CN121651990A
A method for improving performance of a disassembled concrete component based on multi-stage collaborative repair and a product thereof
CN121651990B